AstroAnthropology Meets AstroTheology: Lucas Mix, Shoaib Malik, and Andrew Davis - Peters, Ted (Zygon, 2025)
The 2024 Institute on Religion in an Age of Science Summer Conference at Star Island featured the future of the human race on Earth as we travel to off-Earth locations and make contact with extraterrestrial neighbors. Scholars Lucas Mix, Shoaib Ahmed Malik, and Andrew Davis provide Zygon: Journal of Religion and Science with articles that engage the space sciences with philosophical, theological, and ethical analysis along with constructive proposals.